Macroprudential and Microprudential Policies : Toward Cohabitation - Osinski, Jacek (Staff Discussion Notes; Staff Discussion Notes ;, 2013)
Effective arrangements for micro and macroprudential policies to further overall financial stability are strongly desirable for all countries, emerging or advanced. Both policies complement each other, but there can also be potential areas of overlap and conflict, which can complicate this cooperation. Organizing their very close interactions can help contain these potential tensions. This note clarifies the essential features of macroprudential and microprudential policies and their interactions, and delineates their borderline. It proposes mechanisms for aligning both policies in the pursuit of financial stability by identifying those elements that are desirable for effective cooperation between them. The note provides general guidance. Actual arrangements will need take into account country-specific circumstances, reflecting the fact that that there is no 'one size fits all.'.